Evaluation of linkage disequilibrium, population structure, and genetic diversity in the U.S. peanut mini core collection - Otyama, P.I.; Wilkey, A.; Kulkarni, R.; Assefa, T.; Chu, Y.; Clevenger, J.; O’Connor, D.J.; Wright, G.C.; Dezern, S.W.; MacDonald, G.E.; Anglin, Noelle L.; Cannon, Ethalinda K.S.; et al. (Springer, 2019)
Background Due to the recent domestication of peanut from a single tetraploidization event, relatively little genetic diversity underlies the extensive morphological and agronomic diversity in peanut cultivars today. To broaden the genetic variation in future breeding programs, it is necessary to characterize germplasm accessions for new sources of variation and to leverage the power of genome-wide association studies (GWAS) to discover markers associated with traits of interest. We report an analysis of linkage disequilibrium (LD), population structure, and genetic diversity, and examine the ability of GWA to infer marker-trait associations in the U.S. peanut mini core collection genotyped with a 58 K SNP array.